Computational Study of Hydrogen Bonding in CH3CN•••H-X (X=OH, F, Cl, NH2) Complexes - Sapkota, Dhurba; Parajuli, Rajendra (Amrit Research Journal, 2021)
In this work, first principles study of acetonitrile complexes (acetonitrile•••H-X, X=F, Cl, NH2, OH) has been carried out using electrostatic potential analysis, ab initio (MP2/6-311++g(2d, 2p), B3LYP/6-311++g(2d, 2p) and AIM theoretical calculations and these calculations confirm the hydrogen bonding interaction for these complexes. The geometrical parameters, binding energy and (3, -1) bond critical points confirm that HF donor is found to form strong hydrogen bond and NH3 donor is found to form weaker hydrogen bond for these complexes.